Physical design of quantum circuits in ion trap technology – A survey. (September 2016) - Mohammadzadeh, Naser
Abstract: Quantum circuits have indicated incredible potential for having the capacity to take care of specific issues, which are unmanageable on classical machines. Research in quantum circuit design distinguishes between logic synthesis and physical design. In this survey, we review the approaches, exact and heuristic, proposed for physical design automation of quantum circuits in ion-trap technology that is one of the most advanced quantum technologies. We finish up the review by sketching out major open problems for quantum circuit design.